Neutralization of highly acidic crude oil utilizing 2-methylimidazole in polyethylene glycol solution / Norshahidatul Akmar Mohd Shohaimi and Nur Syafiqah Afiqah Ishak - Mohd Shohaimi, Norshahidatul Akmar; Ishak, Nur Syafiqah Afiqah (Universiti Teknologi MARA Cawangan Pahang, 2020)
The naphthenic acids (NA) compound occurs naturally in the acidic crude oil and lead to corrosion problem in the oil refinery. Various methods can be used to reduce the NAs concentration in acidic petroleum crude such as catalytic decarboxylation, dilution or caustic washing but all these methods have its own weaknesses. The main objective of this study is to reduce total acid number (TAN) value of crude oil through neutralization process using catalyst and reagents. The parameters studied were catalysts calcination temperature, catalyst loading and reagent concentration. The acid removal agent used was a mixture of 10% 2- methylimidazole in polyethylene glycol (PEG) with reagent concentration of 100, 500, 1000 and 1500 ppm. Calcium was chosen as a base for the catalyst while Cu and Ni were used as a dopant. The potential catalyst was characterized by FTIR and TGA-DTG for its physical and chemical characteristics. Catalyst with calcination temperature of 1000C, 7 beads of catalyst loading, 500 ppm of 2-methylimidazole in PEG, reaction temperature (35C) and 5 minutes reaction times showed 97% deduction of TAN value from 3.93 to 0.13 mg KOH/g.